2021
DOI: 10.1186/s41043-021-00242-1
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight and obesity among the Saudi population: a case-control study among school children

Abstract: Background Childhood obesity is a global public health concern with major consequences. In Saudi Arabia, the percentage of children who are overweight or obese has significantly increased in the past two decades, raising concerns about the physical and psychosocial consequences of this burden. This study aimed at investigating the different risk factors contributing to childhood obesity in Saudi Arabia. Methods A case-control study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
16
0
3
Order By: Relevance
“…It appears that the prevalence of overweight and obesity among Saudi children and adolescents has been rising over the last decades ( 9 , 10 ). Recently, it was observed that the most important risk factors for obesity among Saudi children 5–9 years-of-age are parental characteristics, awareness of the degree of obesity burden, and lifestyle behaviors, such as frequent snacking, physical inactivity, and screen time ( 27 ). Also, among Saudi children and adolescents, obesity and other risk factors were found to have a significant impact on abnormal glucose metabolism ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the prevalence of overweight and obesity among Saudi children and adolescents has been rising over the last decades ( 9 , 10 ). Recently, it was observed that the most important risk factors for obesity among Saudi children 5–9 years-of-age are parental characteristics, awareness of the degree of obesity burden, and lifestyle behaviors, such as frequent snacking, physical inactivity, and screen time ( 27 ). Also, among Saudi children and adolescents, obesity and other risk factors were found to have a significant impact on abnormal glucose metabolism ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 63.6% of Hail's population was found to be obese. In addition, the sample population of the poll showed that women outnumbered men by a ratio of 71% to 56.2% [3]. The study by Al-Qahtani [6] revealed a significant incidence of overweight and obesity, which should be treated as a public health issue and addressed with targeted community-level interventions and interdisciplinary activities starting in early infancy as a fundamental prevention program.…”
Section: The Prevalence Rate Of Obesity In Young Societymentioning
confidence: 98%
“…It is stated that intervention strategies should consider screen time, including total screen time, television time, computer time, and smartphone use, to prevent childhood overweight/obesity 21 . There are also studies stating that unhealthy snacks consumed while watching TV are as effective as screen time in the development of obesity 22 . In our study, no relationship was found between obesity and screen time.…”
Section: H Pulat Demi̇rmentioning
confidence: 99%